Perancangan User Interface Website Menggunakan Metode User Centered Design (UCD) Studi Kasus Dao - I Ketut Agus Juliana Juliana; I Nyoman Yudi Anggara (Smart Techno (Smart Technology, Informatics and Technopreneurship), 2021)
Media promotion is very important in a company. One of the promotional media that is currently often used is the website. DAO is one company that uses the internet as a promotional medium. DAO is a company engaged in the field of cosmetics, especially for women, by relying on natural ingredients and products that are environmentally friendly. DAO uses social media as promotional media, so they want to build a website, but DAO still has difficulty building a website. This study aims to create a DAO website design. This research uses the UCD (User Centered Design) method so that the results obtained can answer consumers' needs for purchasing products digitally through the website, of course in line with DAO's goal of wanting to promote through the website. The result of this research is the design of the DAO website User Interface design so that later it can reach more users and of course increase loyalty.